Manajemen Peningkatan Mutu Pendidikan Di Masa Pandemi Covid-19 Pada Madrasah Ibtidaiyah Negeri 5 Bandar Lampung - Agus Pramudia (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
Along with the spread of the COVID-19 pandemic, it has had an impact on education which makes it a challenge to continue to improve the quality of education. The research method uses descriptive qualitative methods through interviews, observations, and documentation. Data were analyzed using the following steps: data reduction, data display, and conclusion/verification). The results of this study obtained an illustration that first, planning for improving the quality of education during the COVID-19 pandemic at MIN 5 Bandar Lampung in accordance with each national education standard, it can be seen that in planning the quality management of education it has been done well by forming a drafting team. curriculum. The implementation of quality management is carried out by compiling a madrasa work program as the basis for implementing madrasa activities. The evaluation of improving the quality of education during the covid 19 period at MIN 5 Bandar Lampung is an activity to obtain certainty whether the implementation of education quality improvement activities during the covid 19 period has been carried out according to the original plan and objectives. The last stage of follow-up is to carry out a total evaluation of the target results and process then make some improvements if it turns out that what we have been doing still has shortcomings starting from planning and evaluating at MIN 5 during the covid 19 pandemic.